1999
DOI: 10.2343/geochemj.33.399
|View full text |Cite
|
Sign up to set email alerts
|

Systematic correlation of the Ce anomaly with the Co/(Ni+Cu) ratio and Y fractionation from Ho in distinct types of Pacific deep-sea nodules.

Abstract: Chemical characteristics of "diagenetic" and "hydrogenous" type deep-sea nodules from the central and northeastern Pacific were studied regarding their Ce anomalies and Y fractionation from heavy REE. Pacific nodules of both types show low Y/Ho ratios less than average shales or chondrites, contrasting to the other marine samples (seawaters, limestones, and phosphorites) having higher Y/Ho ratios than aver age shales or chondrites. The "hydrogenous" type nodules show large positive Ce anomalies up to log(Ce/ C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0
1

Year Published

2000
2000
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(33 citation statements)
references
References 50 publications
0
32
0
1
Order By: Relevance
“…Although the experimental data to allow extraction of this information doesn't yet exist it is possible to comment that whilst Ce 4+ is generally extremely low in natural melt compositions it is enhanced at high fO 2 , in alkaline melts, at low temperatures and possibly with increasing pressures (Burnham and Berry, Thomson et al revision 1 submitted 19/08/2015 16 2014). Therefore it is possible that near solidus MORB melts, which are alkaline carbonatites generated at relatively low temperatures (Thomson et al, 2016) (Ohta et al, 1999). These anomalies are associated with the complexation of yttrium in hydrous fluids/melts (Bau, 1999;1996).…”
Section: Eu Cementioning
confidence: 99%
“…Although the experimental data to allow extraction of this information doesn't yet exist it is possible to comment that whilst Ce 4+ is generally extremely low in natural melt compositions it is enhanced at high fO 2 , in alkaline melts, at low temperatures and possibly with increasing pressures (Burnham and Berry, Thomson et al revision 1 submitted 19/08/2015 16 2014). Therefore it is possible that near solidus MORB melts, which are alkaline carbonatites generated at relatively low temperatures (Thomson et al, 2016) (Ohta et al, 1999). These anomalies are associated with the complexation of yttrium in hydrous fluids/melts (Bau, 1999;1996).…”
Section: Eu Cementioning
confidence: 99%
“…Rare earth elements (REEs) are highly enriched in marine ferromanganese nodules (Piper, 1974;Elderfield et al, 1981;Ohta et al, 1999) and ferromanganese crusts (De Carlo and McMurtry, 1992;Bau et al, 1996). The removal of REE by Fe-Mn oxyhydroxides from seawater into marine suspending particles and sediments is an important geochemical process.…”
Section: Introductionmentioning
confidence: 99%
“…It was found that Fe-Mn oxides, such as deep-sea iron-manganese nodules, could lead to the enrichment of REE [22,23] . A comparison of the ΣREE concentration of AS to corresponding Rb/Sr values and contents of Mn and CaCO 3 showed a strong correlation between each other but with varying coefficients (Figure 7).…”
Section: σRee (La/yb) N and δCe Proxies And Their Paleoclimatic Signmentioning
confidence: 99%